Compression of Color Image Using Quantization Method - Denni Rajagukguk Rajagukguk; Iqbal Panjaitan (Jurnal Info Sains : Informatika dan Sains, 2020)
The development of large-capacity storage media causes people to no longer have problems if they have large files. More so if the file we have is an image file. Nevertheless, sometimes the large file size feels annoying if we have to manage the storage media that we have for various data, thepurpose of this study is to compress color imagery. By using quantization method can be taken, By using data compression then the data capacity will be minimized, Utilization of quantization method will facilitate data compression (image), Image compression with kunatization method in RGB Image can reduce thesize of the compressed file, so as to save storage space(Storage).